Antimicrobial potential of resin matrices loaded with coffee compounds. Issue 3 (25th August 2020) - de Almeida, Sarah A.; Ferracane, Jack L.; da Silva, Eduardo M.; Mushashe, Amanda M.; Merritt, Justin; Rocha, Anderson A.; Noronha‐Filho, Jaime D.; de Almeida, Rayane V.; Poskus, Laiza T.
Abstract: This study evaluated the biological behavior of the coffee compounds Trigonelline (T), chlorogenic acid (C), and nicotinic acid (N), correlating with their release from a resin matrix. Minimum inhibitory concentration (MIC) was evaluated against Streptococcus mutans UA159, and cytotoxicity was assessed by methyl tetrazolium salt on OD‐21 cells. Resin matrices (bisphenol A‐glycidyl‐dimethacrylate/triethylene glycol‐dimethacrylate 70/30 wt%, camphorquinone/ethyl 4‐dimethyl aminobenzoate 0.5/1 wt%) were doped with coffee compounds in different concentrations (10/20/30/40/50 wt%), performing 15 groups (T10‐T50, C10‐C50, N10‐N50), and a control group with no coffee compound. Degree of conversion (DC%) was analyzed by Fourier transform infrared spectroscopy. Antimicrobial properties were evaluated by bioluminescence (Luciferase assay). The release from loaded matrices was analyzed over time (24 hr, 6, 14, 21 and 28 days), using high‐performance liquid chromatography (HPLC). Data were submitted to ANOVA/Tukey's test (α = 0.05). MIC for T and C was 6 mg/ml, and 4 mg/ml for N. None of them were cytotoxic. Only T50 and C50 showed lower DC% than control (α < 0.05). Some groups (T30/T40/T50/C40/C50/N50) were strongly antimicrobial, reducing bacterial activity approximately five times compared to control (α < 0.05). For T30, T40, T50, C40, and C50, the HPLC showed a release above or closer to MIC values mainly in 24 hr, but for N50, up to 28 days. In conclusion, the coffee compounds presented antimicrobial activity, depending on their concentration when added in resin matrices, being found a correlation with their release.